Linguagem científica escrita : percursos de apropriação e suas relações com a cultura científica - Santos, Elis Regina Alves dos (2017)
Although the concept of science has changed significantly in recent decades, certain requirements remain essential for the development of scientific practice; notably, the domain of written scientific language is one of them. The appropriation of this language is understood as an integral part of the scientific habitus and it has become core competence for the practice and for the learning of science. That this knowledge is paramount to the longevity of an individual in the scientific field forms the fundamental hypothesis that its acquisition occurs more effectively via students' daily practice, academic or otherwise, than by the focused disciplines or trainings offered at the undergraduate level. As such, the purpose of this research is to investigate the manner in which undergraduate students of the Federal University of São Carlos (UFSCar) – campus São Carlos – appropriate written scientific language and if this can be considered an acquisition strategy of scientific culture. The study is descriptive-exploratory, making use of questionnaires and interviews to collect information, in conjunction with documentary research. The analysis of the results is qualitative-quantitative, using the Content Analysis technique. The results present a verified manner in which to learn written scientific language, seen mainly as instrumental, and suggest its latent potential to constitute as a fundamental element of appropriation of scientific work, which had yet to be developed by the majority of the sample studied and observed.